FACTORS INFLUENCING THE DECISION TO RESIDE IN A RETIREMENT VILLAGE: AN APPROACH USING THE FUZZY DELPHI METHOD - Zaidatul Nadiah Abu Yazid; Nurul Nadia Abd Aziz2; Mohd Aidil Riduan Awang Kader; Mawarti Ashik Samsudin; Azeman Abd Majid (Journal of Islamic, Social, Economics and Development, 2023)
This study addresses the imperative of implementing retirement villages across Malaysia due to the increasing ageing population. It aims to revalidate indicators for the intention to reside in retirement villages and gather consensus and expert opinions on this scale, considering Malaysia's distinct cultures, traditions, and values. The Fuzzy Delphi method, employing a seven-point Likert scale, was utilized to collect data from ten experts across diverse disciplines. Through the analysis of a 23-item questionnaire using triangular fuzzy numbering and the "defuzzification" method, the study determined the ranking of each variable. The findings demonstrated a good level of expert consensus on the indicators for the intention to reside in retirement villages, with an overall agreement exceeding 75%, a threshold value (d) < 0.2, and an α-cut > 0.5. Based on experts' recommendations, priority guidelines were refined by adding or removing items. The findings of this study offer prioritized guidelines, incorporating experts' recommendations by modifying the scale's items. This research holds significant value, contributing to the development of a comprehensive strategy for elderly care and the establishment of retirement villages in Malaysia. Furthermore, it provides crucial insights for non-governmental organizations (NGOs) and the private sector, enabling the facilitation of retirement village development with essential facilities to ensure a favourable and healthy old age for residents. The originality of this study lies in its contextual focus on revalidating indicators tailored to the intention of residing in retirement villages, accounting for Malaysia's cultural intricacies and the relative novelty of retirement village concepts within the country.